Novel calixarene-based surfactant enables low dose split inactivated vaccine protection against influenza infection. Issue 2 (10th January 2020) - Mandon, Elodie Desuzinges; Pizzorno, Andrés; Traversier, Aurélien; Champagne, Anne; Hamelin, Marie Eve; Lina, Bruno; Boivin, Guy; Dejean, Emmanuel; Rosa-Calatrava, Manuel; Jawhari, Anass
Abstract: Influenza A viruses cause major morbidity and represent a severe global health problem. Current influenza vaccines are mainly egg-based products requiring the split of whole viruses using classical detergents such as Triton X-100, which implies certain limitations. Here, we report the use of the novel calixarene-based surfactant CALX133ACE as an alternative to classical detergents for influenza inactivated split vaccine preparation. We confirmed that CALX133ACE-based split HA antigens are fully functional and quantifiable by the "gold standard" method SRID. Additionally, as in the case of the Triton X-100-based split, the CALX133ACE-based split antigens are stable for at least 6 months at 4 °C. Moreover, immunization of mice with CALX133ACE-based split NYMC X-179A (H1N1) antigens harboring 10 to 30-fold less antigen than the commercialized trivalent inactivated vaccines Vaxigrip® or Fluviral® induced comparable efficient protection and neutralizing antibody responses against A(H1N1)pdm09 infection. Taken together, our results demonstrate for the first time the use of a calixarene-based detergent as an efficient splitting agent for the production of optimized influenza split antigens, paving the way for significant improvement in the vaccine manufacturing process, notably with regard to the current regulation on the prohibition of endocrine disruptors, such as Triton X-100.